Application of transient electromagnetic radar in quality evaluation of tunnel composite lining. (20th April 2020) - Ye, Zijian; Zhang, Chengping; Ye, Ying; Zhu, Wenjun
Highlights: A new method to detect insufficient thickness and voids behind lining in tunnel is proposed. Contact status behind the tunnel lining can be determined by the variation of apparent resistivity. Easier to detect the area of lining disease by transient electromagnetic radar (TER) than ground-penetrating radar (GPR). Abstract: Quality evaluation of the composite lining structure is very important for the safe operation of the tunnel. This study applied the transient electromagnetic radar (TER) to evaluate the contact status behind the composite lining structure. The feasibility of TER is verified by the variation of the apparent resistivity in the composite lining based on the one-dimensional (1D) forward calculation and physical simulation. The results of TER in the detection of voids and insufficient thickness is validated by the drilling test. A comparative test is conducted at the same location with quality problems using ground-penetrating radar (GPR). The results show that: (i) the TER is able to detect the insufficient lining thickness and voids behind the tunnel composite lining, contact status between composite lining and surrounding rocks can be determined by the variation of apparent resistivity; (ii) due to the difference of apparent resistivity, test image of TER shows clearly the boundary between surrounding rocks, primary and secondary lining, and voids, which made TER easier than GPR to detect the area of insufficient thickness and voids; (iii) combined with the drilling test results, TER and GPR results are generally consistent with the actual situation. The research and development of TER provides a new idea for the detection and evaluation of the tunnel lining diseases.